Parental Involvement and Digital Competence as Predictors of Academic Commitment - Ladesma, Kimberly; Ocay, Raynard B. (Randwick International of Education and Linguistics Science Journal, 2025)
This research aims to examine the connection of parental involvement and digital competence in educational setting and how they are influenced by academic commitment. The objectives of this study are to evaluate the levels of parental involvement, digital competence, and academic commitment, and identify the major links and intervening effects among these variables. Descriptive-correlational design is employed in this study and targeted a total of three hundred (300) respondents. The researcher used a stratified random sampling technique using Slovin’s formula to get the ideal sample size targeting 18 years old and above senior high school students in three public secondary schools in Loreto, Agusan del Sur. In person meetings are used to administer questionnaires to ensure reliability of the data. Data was analyzed using descriptive and inferential statistics. The study’s results indicated that there were high levels of parental involvement, digital competence and academic commitment. Parental Involvement had a significant relationship with academic commitment, also digital competence had a significant relationship with academic commitment. Furthermore, this means that parental involvement and digital competence predicts academic commitment as indicated by the correlation analysis. The study implies that the combination of high parental involvement and proficient digital competence in teaching forms a supportive framework that significantly boosts students’ academic commitment. Therefore, the study indicates that collaborative effort between parents and educators a conducive learning environment. Parents should provide encouragement, model positive behaviors, and attend school meetings; teachers should undergo professional development in digital literacy.